The Influence of The Child-Friendly District Program on The Fulfillment of Children's Rights in Banyumas District - Rahtami Susanti; Widya Nirmalawati (UM Purwokerto Press, 2023)
Children play an important role in the future of a country, therefore the state has an obligation to protect their rights. Various child protection efforts through the issuance of legislation and concrete programs based on child protection have been carried out by the government. One of the child protection-based government policies implemented in the regions is the child-friendly district program. In 2021, the Banyumas Regency Government was successfully confirmed as a Child Friendly Regency. The objectives of the research are to determine the indicators that must be met by Banyumas Regency in order to be designated as a Child Friendly Regency, to find out how to create a child-friendly village regulation and to analyze the effect of the Child Friendly Regency Program on the fulfillment of children's rights in Banyumas Regency. The output of this research is an article in the national journal Sinta 6, namely Idea Law, Faculty of Law, Universitas Jenderal Soedirman Purwokerto, articles in proceedings with ISBN and copyright of scientific articles.